(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article describes in detail the issue of “Psychological foundations of the development of students’ oral speech and thinking in the process of designing and teaching basic concepts.” Designing and teaching of basic concepts implies the systematic presentation of the basic concepts necessary for students to acquire complex and precise knowledge during the educational process. This approach ensures that the student’s knowledge is identified, compared and deeply understood. The opinions of psychologists about the cognitive process, emotional cognition, logical cognition, as well as their opinions on the formation of mathematical concepts are presented.